Expert Consensus on the Management of Adverse Events During Treatment with Lenvatinib for Thyroid Cancer. Issue 5 (May 2020) - Reed, N.; Glen, H.; Gerrard, G.; Good, J.; Lei, M.; Lyon, A.R.; Strachan, M.; Wadsley, J.; Newbold, K.
Abstract: Aims: Lenvatinib is an oral multi-kinase inhibitor approved for the treatment of adults with progressive, locally advanced or metastatic, differentiated thyroid carcinoma refractory to radioactive iodine. Materials and methods: A literature review was undertaken to inform the development of consensus-based guidance for the routine management of adverse events associated with lenvatinib. PubMed was searched on 24 October 2017; the search terms were 'lenvatinib' and 'thyroid cancer'. Results: Hypertension, diarrhoea, weight loss, skin toxicities and cardiovascular adverse events were considered. For grade 1/2 diarrhoea, initial treatment should be loperamide with a 1-week treatment interruption if diarrhoea persists and dose reduction if diarrhoea recurs on reinitiation of lenvatinib. Blood pressure should be monitored daily in patients with pre-existing hypertension, otherwise from 1 week after the initiation of lenvatinib and weekly for the first 2 months. For patients with systolic blood pressure ≥135 mmHg to <160 mmHg or diastolic blood pressure ≥85 mmHg to <100 mmHg, lenvatinib should be continued but antihypertensive therapy initiated/intensified. For patients who remain hypertensive, a treatment break can be considered with lenvatinib reinitiated at a reduced dose once the patient's blood pressure has stabilised for at least 48 h. Weight loss of 10% of baseline body weight or the onset of anorexia should be managed with a 1-week treatment break; patients should maintain a healthy, active lifestyle. For patients with grade 2 proteinuria, lenvatinib may be continued, but an angiotensin II receptor blocker or angiotensin converting enzyme inhibitor should be commenced. For grade >3 proteinuria, lenvatinib should be interrupted until proteinuria returns to 1+. For chronic proteinuria, lenvatinib should be stopped. Skin toxicities should be managed with moisturisers or emollients and soap substitutes. Conclusions: Prophylaxis, regular monitoring and symptomatic management with appropriate short treatment breaks and, for persistent adverse events, dose reductions, are recommended to enable patients to remain on the optimal dose regimen. Highlights: The following should be monitored during treatment with lenvatinib for thyroid cancer. Prophylaxis, regular monitoring and symptomatic management are recommended to enable patients to remain on the optimal dose regimen. Blood pressure should be monitored daily in patients with pre-existing hypertension, otherwise from 1 week after initiation of lenvatinib and weekly for the first 2 months. Lenvatinib may be continued for patients with emergence of 2 + proteinuria; an angiotensin II receptor blocker or angiotensin converting enzyme inhibitor should be commenced. Skin toxicities should be managed with moisturisers or emollients and soap substitutes.